2020
DOI: 10.3390/nu12072135
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Deficiency and Brain Accumulation of S-Adenosylhomocysteine in Thioacetamide-Induced Acute Liver Failure

Abstract: Background: Acute liver failure (ALF) impairs cerebral function and induces hepatic encephalopathy (HE) due to the accumulation of neurotoxic and neuroactive substances in the brain. Cerebral oxidative stress (OS), under control of the glutathione-based defense system, contributes to the HE pathogenesis. Glutathione synthesis is regulated by cysteine synthesized from homocysteine via the transsulfuration pathway present in the brain. The transsulfuration-transmethylation interdependence is controlled by a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The ratio of AdoMet to AdoHcy is frequently considered a metabolic gauge controlling in vivo methylation reactions, where a decrease in this ratio predicts reduced methylation capacity ( Czarnecka et al, 2020 ). These methylations are required for the 5′-cap formation of viral mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of AdoMet to AdoHcy is frequently considered a metabolic gauge controlling in vivo methylation reactions, where a decrease in this ratio predicts reduced methylation capacity ( Czarnecka et al, 2020 ). These methylations are required for the 5′-cap formation of viral mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is a nonprotein-forming amino acid that can activate ionotropic glutamate N-methyl-aspartate (NMDA) receptors, thereby causing Ca 2+ to flow into neurons, which in turn activates several pathways, triggers oxidative stress, inflammation and apoptosis, and causes excitotoxicity [ 10 ]. Elevated levels of homocysteine in the plasma and brain develop hyperhomocysteinemia.…”
Section: Introductionmentioning
confidence: 99%
“…To verify whether rutin regulates ferroptosis in VILI mice, we performed a nontargeted metabolomic analysis of VILI model mice treated with rutin, and the results showed that rutin intervention increased the amount of glutathione disulfide (also known as oxidized glutathione) and decreased the amount of AdoHcy. AdoHcy is a competitive inhibitor of s‐adenosylmethionine (AdoMet)‐dependent trans‐methylation reactions, and the ratio of AdoMet/AdoHcy is predictive of the cellular methylation status (Czarnecka et al, 2020; Zanatta et al, 2017). AdoHcy can deplete cysteine, which is the metabolic precursor of glutathione, thus causing oxidative stress and reducing glutathione (Czarnecka et al, 2020; Zanatta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AdoHcy is a competitive inhibitor of s‐adenosylmethionine (AdoMet)‐dependent trans‐methylation reactions, and the ratio of AdoMet/AdoHcy is predictive of the cellular methylation status (Czarnecka et al, 2020; Zanatta et al, 2017). AdoHcy can deplete cysteine, which is the metabolic precursor of glutathione, thus causing oxidative stress and reducing glutathione (Czarnecka et al, 2020; Zanatta et al, 2017). These results suggested that rutin may increase glutathione levels in the lung tissues of VILI mice.…”
Section: Discussionmentioning
confidence: 99%